Literature Review : The Role of Digital Technology in Enhancing Entrepreneurship in the Era of Industry 4.0 - Arijo Isnoer Narjono (International Forum of Researchers and Lecturers, 2025)
This study examines the role of digital technology in enhancing entrepreneurship in the Era of industry 4.0 through a systematic literature analysis of various sources from 2013 to 2023. By adopting this methodological approach, the research elucidates the benefits, challenges, and solutions associated with the adoption of digital technology for business practitioners, particularly in the micro, small and medium enterprises (MSMEs). The analysis demonstrates that digital technology significantly enhances operational efficiency, productivity, and market reach, while also fostering innovation in business models. However, challenges such as resource limitations, a lack of digital literacy, and the digital divide persist as significant obstacles. Furthermore, the study identifies strategic solutions to mitigate these challenges, including digital literacy training, technology subsidies, and improvements to digital infrastructure. The limitations of this research include a constrained data range from 2013 to 2023 and insufficient exploration of practical dimensions and ethical issues pertaining to the adoption of digital technology. Future research is encouraged to investigate these topics in greater depth, particularly within localized contexts and their implications for business sustainability. These findings underscore the critical role of digital technology as a fundamental enabler for developing competitive and sustainable entrepreneurship in Era 4.0.